Patient Safety Competency : Nursing Care for Prevention with Catheter-Associated Urinary Tract Infection for New Graduated Nurses - Yaprom, Chulaporn; Chuamanochan, Nunthida (Journal of The Royal Thai Army Nurses, 2024)
This academic article writes about the development of effective and safe patient care. Therefore, patient safety performance development needs to be focused on building patient care capabilities with information around the side. It is intended to provide information on performance, patient safety, and nursing to prevent urinary tract infections in patients who are putting on a garden line for newly completed nurses. So, patient security performance development must focus on building capacity for care of patients for the newly finalized nurse, highlighting safety priorities. Can properly care for patients according to professional principles. The author very much hopes that this information will be useful to nurse administrators, professional nurses, and midwives who need to understand and perceive information related to the development of performance, safety of patients of such newly graduated nurses in order to keep patient care of quality and effectiveness.